Factores psicosociales y el aprendizaje en los estudiantes de la básica media en la Unidad Educativa Urdaneta de la Parroquia Ricaurte - Alvarado Cedeño, Ingrid Nayeli (2024)
Psychosocial factors constitute a significant issue that negatively impacts students' learning processes and the overall quality of social interaction. Globally, scientific literature has yielded results elucidating the nature, characteristics, and factors associated with this problem. However, in nations with limited resources and in the midst of development, where the situation is even more critical, there is a noticeable lack of awareness regarding this phenomenon. The current study is conducted at the Urdaneta Educational Unit, located in the district of Los Ríos province, specifically in the Ricaurte parish. It has been observed that students face difficulties in their learning process, prompting the need to understand how psychosocial factors influence these issues. The research adopts a descriptive, cross-sectional, and propositional methodology, involving a sample of 90 high school students. The objective is to analyze and propose measures to mitigate the impact of psychosocial factors in the educational context.